2004
DOI: 10.1161/01.hyp.0000103630.72812.10
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Treatment and Control in Five European Countries, Canada, and the United States

Abstract: Abstract-Levels

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

36
579
7
47

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 957 publications
(682 citation statements)
references
References 32 publications
(24 reference statements)
36
579
7
47
Order By: Relevance
“…Of these, 41% receive an antihypertensive treatment that results in 60% and 30% response rates at thresholds of 160/95 and 140/90 mmHg respectively. This leads to the most unfavourable situation that only 8% of all hypertensive individuals are controlled at guideline levels of <140/ 90 mmHg (Wolf-Maier et al 2004). Under these conditions, genetic abnormalities that markedly impact blood pressure variation should also materialize as stroke genes.…”
Section: Hypertension and Strokementioning
confidence: 99%
“…Of these, 41% receive an antihypertensive treatment that results in 60% and 30% response rates at thresholds of 160/95 and 140/90 mmHg respectively. This leads to the most unfavourable situation that only 8% of all hypertensive individuals are controlled at guideline levels of <140/ 90 mmHg (Wolf-Maier et al 2004). Under these conditions, genetic abnormalities that markedly impact blood pressure variation should also materialize as stroke genes.…”
Section: Hypertension and Strokementioning
confidence: 99%
“…2 However, data from national surveys and other sources suggest a high prevalence of uncontrolled hypertension, with up to two-thirds of individuals with hypertension being inadequately treated. 3 All current hypertension treatment guidelines agree that the major benefit of treatment is associated with improved BP control. The European guidelines (ESH/ESC, 2007) suggest that all five major classes of anti-hypertensive agents are suitable for the initiation and maintenance of antihypertensive treatment, and furthermore suggest that, because many patients require more than one drug, emphasis on identification of the first class of drugs to be used is often futile.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain adequate BP reduction, in particular over the entire 24-h period, a combination of two or more antihypertensive drugs is required in most patients. [1][2][3]5,18 Combinations involving a CCB with a blocker of the renin-angiotensin-aldosterone system (RAAS), for example, an ARB or ACE-I, are among those recommended by the guidelines 19,20 and are becoming increasingly used in clinical practice. Their usefulness is based on a favorable pharmacodynamic profile (different mechanisms of antihypertensive action favor efficacy, while RAAS blockade counteracts edema formation caused by dihydropyridines), which translates into clinical benefits in terms of effectiveness in achieving BP control and tolerability.…”
Section: Discussionmentioning
confidence: 99%
“…1-3 However, most patients do not achieve target BP levels, and the majority of them require combination therapy with two or more drugs in order to obtain an adequate BP reduction. [1][2][3][4][5] The ACCOMPLISH (Avoiding Cardiovascular events through COMbination therapy in Patients Living with Systolic Hypertension) study has shown that treatment with the combination of an angiotensin-converting enzyme inhibitor (ACE-I) and a calcium channel blocker (CCB) may not only be effective in achieving BP control and well tolerated, but may also reduce cardiovascular event rates to a larger extent than an ACE-I plus diuretic combination. 6 Single-pill combinations of CCBs and angiotensin II receptor blockers (ARBs) are now available and have been reported to be widely used, well tolerated and effective treatments for controlling BP.…”
Section: Introductionmentioning
confidence: 99%